Environmental Friendly Analysis on Fishing Gear of Trammel Net in Cilacap, Central Java - Sutriyono Sutriyono; Marsoed Marsoed; Aminudin Afandhi (Indonesian Journal of Environment and Sustainable Development, 2017)
The purpose of this study was to analysis about the composition of the catch, the selectivity of fishing gear and fishing gear level of friendliness to the environment. The data collection is done by experimental fishing.  Selectivity analysis applied by  Shannon diversity index and Simpson dominance index. Analysis of scoring was used to rate the friendliness of fishing gear on the environment. The main target of the catch composition (33.93%) and the by catch (66.07%) of the catch species diversity index was 2,16 to 2,78 (high diversity index; the selectivity of fishing gear is low). Dominance index was 0,36 to 0,50 (did not happen dominance species catches). The total value of the scoring is based on the criteria of degree of friendliness of fishing gear on the environment is the 26 included in the category of less environmentally friendly fishing gear. The catch is dominated by small fish. If it lasts for a long time and continuously, it can adversely affect the conservation of fish resources. It should be a mechanism for management systems such as open and close an area to fishing operations or modifications to fishing gear mechanism which can reduce the yield of bycatch and small ones.Keywords: composition, diversity, dominance and environmentally friendly, selectivity